THE ROLE OF MENTORING IN THE FAMILY HOPE PROGRAMME (PKH) IN PERCUT SEI TUAN SUBDISTRICT, DELI SERDANG REGENCY, PROVINSI SUMATERA UTARA - Marini Afifah Lubis; Zulkifli; Bengkel (RADJA PUBLIKA, 2024)
Poverty, which is an obstacle to development, is characterized by limitations, a lack of ability, and many shortcomings. Limitations, for example, in gaining freedom to live according to the level of life expectancy, inability to get an education, get access to adequate health, and experience shortcomings in fulfilling basic needs both clothing and food. Poverty is considered the inability to fulfill basic food and non-food needs, measured in terms of expenditure. One of the government programs to alleviate poverty is the Family Hope Program (PKH), which is run based on Law No. 40 of 2004 concerning Social Security, Law No. 11 of 2009 concerning social welfare, Presidential Instruction No. 3 of 2010 concerning equitable development programs, Presidential Regulation No. 15 of 2010 concerning the acceleration of poverty reduction, and Law No. 39 of 1999 concerning human rights. PKH is a family-based social protection model. This research uses descriptive methods with a qualitative approach. It was conducted in Percut Sei Tuan District, Deli Serdang Regency. The research was carried out in May–June 2023. The results of this study The role of community facilitators through the Family Hope Program (PKH) is that of someone who makes himself a mediator, facilitator, educator, enabler, and also a representative for the community who strives for the community as PKH members to be able to help, especially in overcoming poverty in Percut Sei Tuan District. There are several roles carried out by PKH assistants, especially in overcoming poverty, including the Role as rescuer, Role as provider, Role as modernizer, Role as liberator, Role as catalyst, Role as fasilitator, Role as ally, Role as advocate.